2021
DOI: 10.1108/jfmm-04-2021-0088
|View full text |Cite
|
Sign up to set email alerts
|

Social and environmental concerns within ethical fashion: general consumer cognitions, attitudes and behaviours

Abstract: PurposeAlthough interest in sustainability within the fashion apparel industry has increased over the last decade, ethical fashion remains a minority trend due to low consumer awareness and consumption behaviour. The aim of the paper is to explore empirically the relationships between general consumer support for ethical fashion, buying intention and willingness to pay, focussing on the effect that consumer concern and knowledge and beliefs have on these variables.Design/methodology/approachData were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
0
7
0
5
Order By: Relevance
“…Further research is suggested for exploring the factors that impact consumer psychology (e.g. Pérez et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Further research is suggested for exploring the factors that impact consumer psychology (e.g. Pérez et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Returning to the concept of consumer brand engagement, it is important to acknowledge that brands play a central role in this concept, with engagement being an integral part of the consumer‐brand relationship. The literature review highlights the prominence of a three‐dimensional approach and the utilization of scales derived from this theoretical framework (Pérez et al, 2022). Lourenço et al (2022) explain that the theoretical discussion on the subject seems to accept that three dimensions (cognitive, affective, and behavioral) are the result of the generation of psychological conditions of interest, that is, internal and mental conditions (represented not by bodily reactions but by experienced personal states, difficult to describe and identify).…”
Section: Research Hypotheses and Conceptual Frameworkmentioning
confidence: 99%
“…E-social interaction is considered a prerequisite for making purchase decisions (Mo et al , 2018; Sun et al , 2022). E-social interaction has contributed to the e-WOM literature by examining customers’ interactions with e-WOM (Choi et al , 2019; Jun et al , 2017) and SMI selectivity of e-commerce and its impact on consumer purchase intention in e-commerce (Gunawan and Huarng, 2015; Hajli, 2014; Pérez et al , 2022). Thus, the authors conceptualize e-social interactions in social commerce environments into two forms: e-WOM communication and observing other consumers’ purchases with SMI.…”
Section: Literature Review and Development Of The Research Frameworkmentioning
confidence: 99%
“…To take advantage of the cognitive factors and e-social interactions in influencing green purchase intention, firms should take the initiative to encourage customers to use social media as voluntary contributions (Li et al , 2021). Some scholars have revealed that social media could encourage individuals to share information through virtual platforms (Sun and Wang, 2020), and e-WOM has become a valuable reference that affects purchase intention (Leong et al , 2022; Pérez et al , 2022; Sharif and Yeoh, 2018).…”
Section: Introductionmentioning
confidence: 99%